Community pharmacy medication review, death and re-admission after hospital discharge: a propensity score-matched cohort study. Issue 1 (8th August 2019) - Lapointe-Shaw, Lauren; Bell, Chaim M; Austin, Peter C; Abrahamyan, Lusine; Ivers, Noah M; Li, Ping; Pechlivanoglou, Petros; Redelmeier, Donald A; Dolovich, Lisa
Abstract : Background: In-hospital medication review has been linked to improved outcomes after discharge, yet there is little evidence to support the use of community pharmacy-based interventions as part of transitional care. Objective: To determine whether receipt of a postdischarge community pharmacy-based medication reconciliation and adherence review is associated with a reduced risk of death or re-admission. Design: Propensity score-matched cohort study. Setting: Ontario, Canada Participants: Patients over age 66 years discharged home from an acute care hospital from 1 April 2007 to 16 September 2016. Exposure: MedsCheck, a publicly funded medication reconciliation and adherence review provided by community pharmacists. Main outcome: The primary outcome was time to death or re-admission (defined as an emergency department visit or urgent rehospitalisation) up to 30 days. Secondary outcomes were the 30-day count of outpatient physician visits and time to adverse drug event. Results: MedsCheck recipients had a lower risk of 30-day death or re-admission (23.4% vs 23.9%, HR 0.97, 95% CI 0.95 to 1.00, p=0.02), driven by a decreased risk of death (1.7% vs 2.1%, HR 0.79, 95% CI 0.73 to 0.86) and rehospitalisation (11.0% vs 11.4%, HR 0.96, 95% 0.93–0.99). In a post hoc sensitivity analysis with pharmacy random effects added to the propensity score model, these results were substantially attenuated. There was no significant difference in 30-day return to the emergency department (22.5% vs 22.8%, HR 0.99, 95% CI 0.96 to 1.01) or adverse drug events (1.5% vs 1.5%, HR 1.03, 95% CI 0.94 to 1.12). MedsCheck recipients had more outpatient visits (mean 2.11 vs 2.09, RR 1.01, 95% CI 1.00 to 1.02, p=0.02). Conclusions and relevance: Among older adults, receipt of a community pharmacy-based medication reconciliation and adherence review was associated with a small reduced risk of short-term death or re-admission. Due to the possibility of unmeasured confounding, experimental studies are needed to clarify the relationship between postdischarge community pharmacy-based medication review and patient outcomes.